Hamsters with long COVID present distinct transcriptomic profiles associated with neurodegenerative processes in brainstem - Anthony Coleon; Florence Larrous; Lauriane Kergoat; Magali Tichit; David Hardy; Thomas Obadia; Etienne Kornobis; Hervé Bourhy; Guilherme Dias de Melo (Nature Communications)
Abstract Following infection with SARS-CoV-2, patients may experience with one or more symptoms that appear or persist over time. Neurological symptoms associated with long COVID include anxiety, depression, and memory impairment. However, the exact underlying mechanisms are not yet fully understood. Using golden hamsters as a model, we provide further evidence that SARS-CoV-2 is neuroinvasive and can persistently infect the brain, as viral RNA and replicative virus are detected in the brainstem 80 days after the initial infection. Infected hamsters exhibit a neurodegenerative signature in the brainstem, characterized by overexpression of innate immunity genes, and altered expression of genes involved in the dopaminergic and glutamatergic synapses, in energy metabolism, and in proteostasis. These infected animals exhibit persistent depression-like behavior, impaired short-term memory, and late-onset signs of anxiety. Finally, we provide evidence that viral and immunometabolic mechanisms coexist in the brainstem of SARS-CoV-2-infected hamsters, contributing to the manifestation of neuropsychiatric and cognitive symptoms.